ANTHONY GIDDENS'S STRUCTURATION THEORY AND RELEVANCE WITH SOCIOLOGY OF KNOWLEDGE - Rifqi Khairul Anam (SOCIAL EDU: Jurnal Ilmu Sosial dan Pendidikan, 2025)
Anthony Giddens's structuration theory serves as a pivotal framework in contemporary social theory, illuminating the intricate relationship between human agency and societal structures. Central to this theory is the "duality of structure," a concept that dissolves the binary opposition between structural determinism and radical individualism by demonstrating how structures simultaneously constrain and are reshaped by individual actions. This study applies structuration theory to the sociology of knowledge, exploring how it explains the processes of knowledge production, dissemination, and institutional dynamics. Through a structured library research methodology, the study synthesizes theoretical and empirical insights across disciplines such as organizational studies and information systems, employing core concepts like agency, recursive practices, and time-space distanciation as analytical tools. The findings underscore the theory's adaptability to complex sociological phenomena, revealing its power to reconcile agency-structure tensions while situating knowledge within its historical and cultural contexts. By leveraging Giddens's framework, the study offers a nuanced understanding of social practices, empowering individuals to critically engage with and transform their sociocultural environments.